Clima laboral y su incidencia en la operatividad en la comercializadora mega proprinec de la ciudad de Babahoyo en el periodo 2020-2021 - Flor Casquete, Zoila Marisela (2022)
The present investigation sought to evaluate the incidence of the work environment in the operation of the MEGA PROPRINEC marketer, questioning evidence that must be improved such as training, communication between collaborators, multidisciplinary work and motivation techniques, which will allow the work to meet the expectations and obtain a friendly work environment. This study cataloged as mixed qualitative-quantitative, it was necessary to resort to information from several authors, types and research methods such as: inductive, deductive and historical - logical method, to obtain the information techniques were used such as interviewing the General Manager, Chief of inventory and Supervisor of the financial administrative department, in addition to surveys of employees belonging to the department, was evaluated using the Ishikawa theory, work environment consolidation matrix and SWOT. The results show that the climate in the company is not ideal, which causes job dissatisfaction and breach of business objectives, there is a direct relationship between the work environment and the operability of the workers of the MEGA PROPRINEC marketer, since an inadequate climate causes job dissatisfaction as well as the failure to meet the objectives set, thus altering the levels of emotional stability and performance in their workers